Behavioural changes in African elephants in response to wildlife tourism - Szott, I. D.; Pretorius, Y.; Koyama, N. F. (Journal of zoology (1987), 2019)
Eco‐tourism and human–wildlife interaction can lead to increases in stress, vigilance and aggression in many species, however, studies investigating wildlife viewing are scarce. We present the first study investigating the impact of wildlife tourism on African elephant, Loxodonta africana, behaviour. Over 15 months, we studied the effect of monthly tourist pressure (tourist numbers) on the occurrence of stress‐related, vigilance and conspecific‐directed aggressive behaviour in 26 individually identified elephants and the effect of up to three vehicles on the direction of travel of non‐identified herds using 5‐min continuous focal observations. We analysed the effect of tourist pressure and vehicle presence using generalized linear mixed models, including habitat type, herd type and size and season, as well as sex and age for behaviour models, as additional factors. We found no effect of factors on stress‐related behaviour, but elephants were more likely to perform vigilance behaviours at waterholes compared to other habitat types. As tourist pressure increased, conspecific‐directed aggression in elephants increased and male elephants were more likely to perform conspecific‐directed aggression compared to female elephants. Furthermore, we found that elephant herds became increasingly likely to move away with increasing numbers of vehicles present. Results suggest that reserves should monitor elephant behaviour to identify when tourist pressure has potential effects on elephant welfare and train guides to monitor behaviour and adjust minimum distances flexibly to ensure high welfare standards and tourist safety. This study further contributes to a small but growing body of literature on non‐consumptive wildlife tourism impacts on wild animals. Eco‐tourism and human‐wildlife interactions can lead to increases in stress, vigilance and aggression in many species, however studies investigating wildlife viewing are scarce. This study investigated how wildlife tourism affected free‐ranging African elephant behaviour over 15 months in Madikwe Game Reserve, South Africa. High tourist pressure (monthly tourist number in the reserve) was related to an increased likelihood of individual elephants displaying conspecific‐directed aggression. Further, non‐identified elephant herds were more likely to move away from tourists observing them from vehicles with increasing numbers of vehicles present. Non‐consumptive wildlife tourism potentially aids in protection and conservation of species but simultaneously it could have negative effects on elephant welfare and should therefore be monitored closely.